2020
DOI: 10.1109/access.2020.2989128
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Exercise Recognition and Evaluation Based on Smart Sensors With Deep Learning Framework

Abstract: Exercise therapy is seen as one of the major treatments for the rehabilitation for patients, particularly using modern technologies, such as virtual reality or augmented reality. Computer-assisted physical rehabilitation training involves measuring performance by analyzing the movement data collected with a sensory system during prescribed rehabilitation exercises. Human activity recognition is a challenging topic for machine learning in the present area of research. Since the sensor-based activity recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The evaluation elapsed time of the algorithms of literature [ 5 ], literature [ 6 ], literature [ 7 ], literature [ 8 ], literature [ 9 ], and this paper were compared, and the results are shown in Table 3 .…”
Section: Experimental Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation elapsed time of the algorithms of literature [ 5 ], literature [ 6 ], literature [ 7 ], literature [ 8 ], literature [ 9 ], and this paper were compared, and the results are shown in Table 3 .…”
Section: Experimental Analysis and Resultsmentioning
confidence: 99%
“…Analysis of the data in Table 3 shows that with the increasing number of samples, the evaluation time of different algorithms shows an upward trend. The evaluation time of the algorithm in literature [ 5 ] varies from 1.25 s to 1.78 s. The evaluation time of the algorithm in literature [ 6 ] varies from 1.33 s to 1.96 s. The evaluation time of the algorithm in literature [ 7 ] varies from 1.33 s to 2.13 s. The evaluation time of the algorithm in literature [ 8 ] varies from 1.64 s to 2.55 s. The evaluation time of the algorithm in literature [ 8 ] varies from 1.14 s to 1.36 s. Compared with these algorithms, the evaluation time of the algorithm in this paper varies from 0.56 s to 0.91 s, indicating that the evaluation time of the algorithm in this paper is shorter and more efficient.…”
Section: Experimental Analysis and Resultsmentioning
confidence: 99%
“…Jiang et al [50] proposed the use of deep convolutional neural networks (DCNNs) and wearable sensors for human rehabilitation action recognition, aiming to provide patients with better medical care. Zhang et al [51] proposed a patient rehabilitation training recognition system based on intelligent sensors and deep learning to evaluate the advantages and disadvantages of training movements. Lemoyne et al [52] built a traditional gait analysis system that combines the functions of the system with machine learning to classify different types of gaits; this system can help select the right prosthetic limb for a patient during the recovery process.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, many ML and deep learning-based models have been used along with wearable sensors in the assessment of human movement activities in many domains including: health [ 11 ], recreation activities [ 12 ], musculoskeletal injuries or diseases [ 13 ], day-to-day routine activities (e.g., walking, jogging, running, sitting, drinking, watching TV) [ 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], sporting movements [ 22 ] and exercises [ 23 , 24 , 25 , 26 , 27 ]. The ML models used for exercise recognition have predominantly used multiple wearable sensors [ 28 , 29 , 30 , 31 ], specifically in the areas of free weight exercise monitoring [ 32 ], the performance of lunge evaluation [ 24 ], limb movement rehabilitation [ 33 ], intensity recognition in strength training [ 34 ], exercise feedback [ 24 ], qualitative evaluation of human movements [ 28 ], gym activity monitoring [ 29 ], rehabilitation [ 23 , 25 , 33 , 35 ] and indoor-based exercises for strength training [ 36 ]. However, the use of multiple sensors is far from ideal in practice because of cost, negative aesthetics and reduced user uptake [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies [ 46 , 47 , 49 , 51 ] have shown the significant advantage of using deep learning models in the general area of HAR. However, very few studies [ 23 , 25 , 27 , 30 ] appear to have used deep learning models in exercise recognition and repetition counting, and where employed they use multiple CNN models for the repetition counting task. To the best of our knowledge, there are no works reported using a single deep CNN model for exercise recognition and for repetition counting.…”
Section: Introductionmentioning
confidence: 99%